A Systematic Review: Reading Comprehension Intervention for Students with Learning Disability - Farhana Zainudin, Nurul; Mohamad Ashari, Zakiah; Mohd Kosnin, Azlina; Saleh, Sofiazianti (International Journal of Psychosocial Rehabilitation, 2020)
Many interventions have been done on improving learning disability (LD) students’ reading comprehension, but systematic review studies are still less explored. Hence, the researcher decided to conduct a systematic review to identify the type of instruction used by the past researcher. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was used as a methodology in conducting this systematic review. 60 articles from the years 2009 to 2019 were retrieved from five databases. After the screening process, a total of 9 articles were chosen to include in this systematic review. The results from this study showed that most studies used experimental design in conducting intervention. This study also revealed that the read-aloud, read-naturally, and multisyllabic programs were frequently used types of intervention. Implications for this study are that it will give an insight for future researchers in conducting effective intervention studies for students with learning disabilities by choosing the reliable intervention technique.